Legal aspects of contracts and third parties : on third-party rights, transfer of rights, agency and contracts / edited by Jan Biemans, Lorna Richardson. - Biemans, J. W. A. (Jan Willem August), 1974-; Richardson, Lorna (Common core of European private law., 2024)
Legal Aspects of Contracts and Third Parties: On Third-Party Rights, Transfer of Rights, Agency and Contracts contains eleven case studies, designed to address various aspects of the topic of contracts and third parties. It includes examination of contractual clauses for the benefit of a third party, including the ability of the contracting parties to vary or revoke the right in favour of the third party after it has been created; the ability to make the right in favour of the third-party conditional; and the extent to which a third party can rely on a limitation clause in a contract between others. This volume also considers the transfer of contractual rights relating to property after that property has been transferred, as well as assignment of rights under a contract. In addition, it examines principal-agent relations (direct and indirect representation) in concluding and executing contracts and holding property on behalf of another and the effects of the insolvency of the agent on the legal rights of the parties. Actions available to a creditor where a contract is prejudicial to their claim (the actio Pauliana) also feature in the analysis. In addressing these topics, this book takes the intersectionality between various areas of law into account, including contract law, agency, tort law, property law, commercial law, insolvency law, patrimonial law, and other parts of the law of obligations. The volume contains contributions from thirteen legal systems and thus sets out the position in civil, common and mixed legal systems.